2015
DOI: 10.1093/mnras/stu1875
|View full text |Cite
|
Sign up to set email alerts
|

Photometric, astrometric and polarimetric observations of gravitational microlensing events

Abstract: The gravitational microlensing as a unique astrophysical tool can be used for studying the atmosphere of stars thousands of parsec far from us. This capability results from the bending of light rays in the gravitational field of a lens which can magnify the light of a background source star during the lensing. Moreover, one of properties of this light bending is that the circular symmetry of the source is broken by producing distorted images at either side of the lens position. This property makes the possibil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Ingrosso et al (2012Ingrosso et al ( ,2015 evaluated the expected polarization signals for a set of reported high-magnification single-lens and exo-planetary microlensing events as well as OGLE-III events towards the Galactic bulge. Recently, Sajadian and Rahvar (2015) noticed that there is an orthogonal relation between the polarization and astrometric shift of source star position in the simple and binary microlensing events except in the fold singularities and investigated the advantages of this correlation for studying the surface of a source star and spots on it.…”
Section: Polarimetry Microlensingmentioning
confidence: 99%
See 3 more Smart Citations
“…Ingrosso et al (2012Ingrosso et al ( ,2015 evaluated the expected polarization signals for a set of reported high-magnification single-lens and exo-planetary microlensing events as well as OGLE-III events towards the Galactic bulge. Recently, Sajadian and Rahvar (2015) noticed that there is an orthogonal relation between the polarization and astrometric shift of source star position in the simple and binary microlensing events except in the fold singularities and investigated the advantages of this correlation for studying the surface of a source star and spots on it.…”
Section: Polarimetry Microlensingmentioning
confidence: 99%
“…Whereas, the polarization signal of the source is always normal to the lens-source connection line (see e.g. Sajadian and Rahvar 2015). When the lens is entering into an inclined disk normal to the disk semimajor axis (ξ = 90 • ), the polarizations of the disk and source are normal to each other.…”
Section: Polarimetric Microlensing Of Disksmentioning
confidence: 99%
See 2 more Smart Citations
“…When the lens is a binary system (see e.g. , Safizadeh et al 1999, Bozza 2001, Hideki 2002, Sajadian & Rahvar 2015, the number and the position of the images differ from those of the single lens case and the astrometric signal trajectory and the deviation varies depending on on the binary system parameters (i.e., the mass ratio and the component separation).…”
Section: Introductionmentioning
confidence: 99%